Occurrence and Distribution of Microplastics in Soils and Intertidal Sediments at Fildes Bay, Maritime Antarctica - Perfetti-Bolaño, Alessandra; Araneda, Alberto; Muñoz, Katherine; Barra, Ricardo O. (Frontiers in Marine Science, 2022)
Increased human activity in Antarctic Peninsula has generated microplastics contamination in marine systems, however, so far little attention has been paid to soils. We investigate the occurrence of microplastics in 11 surface soils and intertidal sediments collected from the Fildes bay, King George Island. A transect was made in soils of Antarctic stations until Fildes bay (S1-S5). Also, intertidal sediments along shore (IS1-IS5) and a reference sample from Ardley island (IS6) were recollected. All samples were stored at 4°C and, organic matter content, pH and particle size were determined. Particles were counted and classified according shape using metal dissecting forceps and Stereo microscope. Particles were analyzed by Fourier-transform infrared spectroscopy (FT-IR). Both fibers (length: 500-2000 µm) and fragments (length: 20-500 µm) were identified. In soil, fragments reached an average of 13.6 particles/50 ml sample, while fragments where not observed in intertidal sediments but fibers with 1.5 particles /50 ml sample. The principal component analysis shows a relationship between fibers and intertidal sediments, contrary to fragments which show a relationship with soils. Fragments in soils showed differences between soils and intertidal sediments (p=0.003) with a high abundance at site S5, but no significant differences were found for fibers. Particle size varied significantly among soils and intertidal sediments (p=0.0007), and shows a higher size in intertidal sediments (average=706.94 µm). Organic matter differs significantly among soils and intertidal sediments (p=0.006) with higher amounts in soils (average=5.95%). Fragments and organic matter showed a positive correlation (r=0.779), while fibers were more related to the particle size of the samples (r=0.713). Fragments had a phenoxy resin composition and has same appearance, shape and bright orange color, as coatings of the facilities. Fibers had a PET composition and different colors, but also the presence of cotton in the sites surrounding the Frei base effluent. The presence of a fiber on Ardley Island indicates that microplastic contamination has reached protected areas. This is the first study to confirm the presence of microplastics in Antarctic soils and we suggest conducting research efforts to identify their sources and improve the management of human activities and their eventual effects on biota.